Triggered EMG (T-EMG) Values of Pedicle Screws with a Powered Screwdriver vs A Standard Probe in Adolescent Idiopathic Scoliosis Do Not Agree: A Prospective Validation Study. (3rd July 2019) - Garg, Sumeet; Palmer, Claire; Whitmore, Wayne; Cyr, Micaela; Michael, Nicole; Kim, Eun; Boucharel, Willy
ABSTRACT: Triggered electromyography (t-EMG) is a common technique used during spinal instrumentation in surgery for adolescent idiopathic scoliosis. This study tests the validity of t-EMG values obtained with a standard ball-tipped probe after completion of screw placement versus t-EMG values obtained during screw insertion with a powered screwdriver. t-EMG values were collected for screws spanning T7–L5 using both a standard probe and a powered screwdriver. A power analysis determined that a sample size of 300 screws would provide enough precision to estimate limits of agreement within ±2 mA. A monopolar constant current stimulation technique (0.2 ms duration and 3.11 Hz stimulation rate) was used at each level. EMG was acquired with placement of bipolar pairs of subdermal needle electrodes. A Bland-Altman plot was used to assess agreement between threshold readings from the two techniques. Twenty-nine patients were enrolled in this study with 305 screws. t-EMG values measured using a powered screwdriver were on average 1 mA lower than values from a standard probe. When readings less than or equal to 20 mA were considered, the limits of agreement were approximately 4 and 7 mA overall. In total, 28/305 (9%) screws were removed and reinserted, 9/305 (3%) screws were redirected, and 3/305 (1%) screws were aborted based on t-EMG readings. Despite a small overall difference in t-EMG value between the standard probe and screwdriver, there was still large variability in agreement between the two techniques. t-EMG values obtained with a powered screwdriver during screw insertion are not interchangeable with values measured by a probe.